A sociabilidade do capital e o gerenciamento da questao social: o projeto ético-político profissional no cotidiano do assistente social - Brant, Nathalia Lopes Caldeira [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
In the formation process of social worker‟s professional labor, beneath the boundaries of capitalist society, Social Work emerges as a specific labour power specialized in the treatment of social question‟s manifestations. The research tries to comprehend society‟s organizational inner logic, dictated by the process of capital accumulation and growth. Within its genesis and contradictions, Social Work predominantly objectificates its labor in some social and occupational spaces, offered by bourgeois state, which is ruled by capital. However, as a profession, Social Work assumes a position towards a professional project, referred as Ethical and Political Professional Project (EPPP). This position guides social workers‟ professional quotidian, associating them to the working class, as part of it, in opposition to its meaning during its genesis in Brazil. Nevertheless, professional labor meaning has been crossing a revaluation in which it is associated, as a collective project, to a specific societal project, committed to society‟s transformation. Thus, the research seeks to comprehend professional labor when taking in consideration its contradictions and goals among capitalist society‟s determinations, wondering about the ethical, political and social directions proposed by the EPPP. Taking as sample the professionals who compose special social protection‟s equipment of welfare policy in the city of Franca, the research tries to understand professional labor realization taking in consideration its quotidian, its professional formation, its boundaries, its possibilities and the hegemonic position took by social workers as a professional category. Interviewing social workers of the referred equipment and gathering some theoretical references which reveals reality‟s movement and clarifies professional insertion among the manifestations of social question, the research intends to comprehend the determining aspects of the...

No processo de constituição do trabalho profissional do assistente social, no limite da sociedade capitalista, o Serviço Social emerge como determinada força de trabalho especializada no atendimento das manifestações da questão social. A investigação desse trabalho se dá na apreensão da lógica de organização da sociedade, em que se insere, ditada pela acumulação e ampliação do capital. Com uma contradição inerente à gênese da profissão, o Serviço Social objetiva seu trabalho em determinados espaços sócio-ocupacionais, predominantemente, oferecidos por um Estado burguês à mercê do capital. Entretanto, como categoria, assume um direcionamento a partir de um projeto profissional, referenciado no Projeto Ético-Político Profissional (PEP). Esse direcionamento orienta o cotidiano do trabalho do assistente social, associa o profissional à classe trabalhadora e, como parte constituinte dela, em contraposição ao significado da profissão no seu início no Brasil. Porém, o significado do trabalho profissional passa por um processo de reconceituação, vinculando o projeto profissional coletivo a um projeto societário, comprometido com a transformação da sociedade. Dessa forma, o que se objetivou na pesquisa foi apreender o trabalho profissional, ao considerar sua contradição e finalidade, nas determinações da sociedade capitalista, considerando o direcionamento ético, político e social proposto pelo PEP. Tendo como amostra os profissionais que compõem os equipamentos da proteção social especial da política de assistência social no município de Franca, procurou-se apreender a objetivação do trabalho profissional considerando seu cotidiano, sua formação profissional, os limites, as possibilidades e o direcionamento hegemônico da categoria. Com entrevistas dos assistentes sociais desses espaços e também com a apropriação de um referencial teórico que desvela...
Keywords: Serviço social - Aspectos politicos; Prática profissional; Serviço social - Profissão; Assistentes sociais - Ética profissional; Serviço social - Orientação profissional; Política social; Assistência social; Social service